Application of the Sandpaper Letters Assistants Jigsaw Model to Improve Latin Writing Skills in Class I SD Negeri Danupayan Distric Temanggung - Harnum Rukmana Ningrum; Arif Wiyat Purnanto; Rasidi (Urecol Journal. Part A: Education and Training, 2022)
This study aims to determine the application of the jigsaw model with the aid sandpaper letters to improve Latin writing skills for class I SD Negeri Danupayan, Distric Temanggung. This research is a type of classroom action research (CAR) with a jigsaw model. Research subject were selected non-randomly. The samples taken were 22 and 11 boys. Methods of data colletion is done by using observation and tests. Test the validity with expert judgement. Analysis og the data using a quantitative formula for the average value of Tulus Winarsunu. The result showed that there was an increase in the percentage og student Latin writing results, in the pre-cycle only 9,5%, while after doing the first cycle the percentage of latin writing result increased from 9,5% to 74,5% and for the increase in the second cycle was 81,2%. This is reinforced by the existence of a jigsaw model assisted by using media can improve student behavior or effectiveness to be more enthusiastic and active so that communication between studentsd is good and makes students have the character of a sense of responsibility, discipline, hard work, coopartion and respect for the opinons of friends. Based on these data, it can be concluded thet there was a significant increase in students Latin writing in the good category.